2019
DOI: 10.1016/j.apcatb.2019.117764
|View full text |Cite
|
Sign up to set email alerts
|

Red phosphorus decorated and doped TiO2 nanofibers for efficient photocatalytic hydrogen evolution from pure water

Abstract: Highlights A new class of TiO2 nanofiber/red phosphorus (TiO2/RP) nanolayer core/shell heterostructure was fabricated by vaporization-deposition strategy. TiO2/RP exhibits enhanced photocatalytic pure water splitting performance. Decoration of RP extends the optical light harvesting ability.  P 5+ doping induced oxygen vacancies improve the charge separation efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
88
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 159 publications
(94 citation statements)
references
References 60 publications
(86 reference statements)
3
88
0
Order By: Relevance
“…As shown Figure b, the wavelength‐dependent photocatalytic HER rates of PCN@HP(0.4) under different light‐emitting diode (LED) light irradiation (Supporting Information, Figure S12) were pretty consistent with its optical absorption spectrum, indicating that the extended optical absorption by HP was responsible to photocatalytic HER activities in the wide‐spectrum visible light region. Importantly, the PCN@HP(0.4) composite ranks as the best photocatalyst for HER via pure water splitting, as compared to almost all the reported PCN and phosphorus‐based photocatalysts (Figure c; Supporting Information, Table S1) . Specifically, PCN@HP(0.4) displayed a quite high apparent quantum yield (AQY) up to 3.59 % at 420 nm.…”
Section: Resultsmentioning
confidence: 87%
See 4 more Smart Citations
“…As shown Figure b, the wavelength‐dependent photocatalytic HER rates of PCN@HP(0.4) under different light‐emitting diode (LED) light irradiation (Supporting Information, Figure S12) were pretty consistent with its optical absorption spectrum, indicating that the extended optical absorption by HP was responsible to photocatalytic HER activities in the wide‐spectrum visible light region. Importantly, the PCN@HP(0.4) composite ranks as the best photocatalyst for HER via pure water splitting, as compared to almost all the reported PCN and phosphorus‐based photocatalysts (Figure c; Supporting Information, Table S1) . Specifically, PCN@HP(0.4) displayed a quite high apparent quantum yield (AQY) up to 3.59 % at 420 nm.…”
Section: Resultsmentioning
confidence: 87%
“…Correspondingly, the colour changed from light yellow for PCN to dark brown for PCN@HP, which is even deeper than the red colour of HP (Supporting Information, Figure S10). These optical absorption and colour evolution indicated that the hybridization of PCN with HP can greatly improve the optical absorption ability to harvest visible light, thus contributing to the photocatalytic enhancement in the visible‐light region …”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations